Pengaruh Kebiasaan Merokok Terhadap Kesehatan Rongga Mulut Pada Remaja (Cross Sectional Study Pada Pelajar Smk 4 Semarang) - Erni Mardiati; Irmanita Wiradona; Ani Subekti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Teenager is a community with labil aged and often have habitual smoking. The smoking activity has influences on mouth disesae as nicotine, carbon monosyde and tar contained on ciggarete. Number of cigarete per day influence mouth health. The research aim to collect information about tooth colour, volume saliva and gingiva health on teenager has habit light smokers and moderate smokers.Research design was cross sectional survey analytic on 50 students light smokers and 40 students moderate smokers. Initial data about number of cigarete smoke per day and economic status was collected and continued by examination of oral tissue health. The data was analysed descriptively and analitycally with Mann Whitney and Independent t test. Research result shown a differences saliva volume between light and moderate smokers (Mann Whitney, p 0,05); there was a differences tooth colour and gingival index between light and moderate smokers (Independent t, p0,05). (Independent t, p0,05). In moderate smokers, there was an blackist spot on tooth surface, less saliva volume, gingival health less compared to light smokers.